2008
DOI: 10.4315/0362-028x-71.8.1651
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Knowledge and Behaviors of Women, Infant, and Children (WIC) Program Participants in the United States

Abstract: Although the incidence of foodborne illnesses has declined, thousands of cases are still reported in the United States. In conjunction with industry efforts to reduce foodborne pathogens, consumers play an important role in decreasing foodborne illnesses. To assess food safety knowledge and food handling behaviors of low-income, high-risk populations, a study was conducted with participants of the Special Supplemental Food Program for Women, Infants, and Children (WIC). A survey was conducted with 1,598 client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…Some surveys used the Delphi techniques to rank consumer behavior (Hillers, Medeiros, Kendall, Chen, & Dimascola, 2003), while other surveys applied a descriptive analysis (Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;Kwon, Wilson, Bednar, & Kennon, 2008;Nesbitt et al, 2009;Sanlier, 2009). Most of these studies are listed in Redmond and Griffith (2003b).…”
Section: Resultsmentioning
confidence: 99%
“…Some surveys used the Delphi techniques to rank consumer behavior (Hillers, Medeiros, Kendall, Chen, & Dimascola, 2003), while other surveys applied a descriptive analysis (Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;Kwon, Wilson, Bednar, & Kennon, 2008;Nesbitt et al, 2009;Sanlier, 2009). Most of these studies are listed in Redmond and Griffith (2003b).…”
Section: Resultsmentioning
confidence: 99%
“…For example, during focus groups with resource-limited individuals in New Jersey, reported food management practices included removing mold from cheese and grains and removing spoiled parts of fruits and vegetables (Kempson et al , 2003), although the U. S. Department of Agriculture (USDA) advises discarding bread, baked goods, soft fruits and vegetables, and soft cheeses containing visible mold (USDA, 2013). In contrast, a nationwide survey of Special Supplemental Nutrition Program for Women, Infants, and Children participants found that 94% would throw away an entire package of cream cheese or cottage cheese if mold was present (Kwon et al , 2008). Elderly persons may be especially vulnerable to food insecurity due to economic factors, which is concerning because immunecompromising conditions are more common in this population; a systematic review of studies from developed countries found some evidence that food expenditures and intake decreased as individuals transitioned from employment to retirement (Conklin et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It was apparent that food safety training was not adequately provided to volunteers who are members of the general public. Previous studies showed inadequate food handling practices for the general public (Kwon, Wilson, Bednar, & Kennon, 2008;Patil et al, 2005;Redmond & Griffith, 2003). Therefore, the lack of food safety training may present an increased risk for foodborne illness for a large group of people served at these volunteer-run operations.…”
Section: Identified Food Safety Risksmentioning
confidence: 99%